PENGEMBANGAN APLIKASI TOLAK STUNTING DAN EDUKASI PENGGUNAANYA SEBAGAI MEDIA PENINGKAT LITERASI DIGITAL UNTUK MENCEGAH STUNTING DI KONAWE SELATAN - Indalifiany, Astrid; Jabbar, Asriullah; Aspadiah, Vica; Pascayantri, Asniar; Mahmudah, Rifa’atul (BESIRU : Jurnal Pengabdian Masyarakat, 2025)
Stunting is a health problem that has a serious impact on the growth and development of children in Indonesia, including in South Konawe, Southeast Sulawesi, which has a high prevalence of stunting. This community service program aims to improve digital literacy in the community in preventing stunting through the Tolak Stunting application. Activities include stunting education and application socialization as a digital innovation. The approach used includes interactive lectures, leaflet distribution, and application demonstrations. This application provides information about stunting, breastfeeding and MPASI guidelines, nutrition calculators, and related government programs. The results of the program show an increase in public awareness of stunting and the importance of digital literacy in understanding the causative factors and prevention efforts. This success emphasizes the importance of collaboration between digital literacy and health education to overcome stunting in the community..